Shinzo Abe’s Security Policy: A Departure from Defensive Posture? - Szanto, Balazs (AEI Insights, 2021)
The paper seeks to provide a critical examination of Japanese Prime Minister Shinzo Abe’s new defence policy direction. PM Abe’s security policy has been criticised as the return of Japanese militarism, both at home and by neighbouring states, especially the People’s Republic of China. The paper takes a comprehensive look at both the legal changes pursued by the Abe administration (such as Japan’s shift on collective self-defence) and the continued increase of Japan’s defence budget. The review of these steps presented in this paper highlight that these new policy directions fall significantly short of a potential Japanese remilitarisation. This research rather argues that the changes are reactionary to Japan’s changing security environment, and seek to improve Japan’s ability to defend itself by adjusting outdated elements of Japan’s defence posture. On their own they do not constitute a significant threat to other regional powers.